2022
DOI: 10.1002/jmrs.570
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 pandemic and the effect of increased utilisation of mobile X‐ray examinations on radiation dose to radiographers

Abstract: Introduction The use of ionising radiation results in occupational exposure to medical imaging professionals, requiring routine monitoring. This study aims to assess the effect of increased utilisation of mobile X‐ray units, mobile imaging of non‐routine body regions and radiographer work practice changes for impact on staff radiation dose during the early stages of the COVID‐19 pandemic. Methods A retrospective analysis of general radiology departments across two metro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…At the same time, in Singapore, there was a three-fold increase in emergency department mobile imaging usage[ 30 ]. Although mobile imaging utilisation increased, there was little change in radiographer-reported doses[ 31 ]. There was a slight shift in imaging regions other than the chest (data not shown)[ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, in Singapore, there was a three-fold increase in emergency department mobile imaging usage[ 30 ]. Although mobile imaging utilisation increased, there was little change in radiographer-reported doses[ 31 ]. There was a slight shift in imaging regions other than the chest (data not shown)[ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although mobile imaging utilisation increased, there was little change in radiographer-reported doses[ 31 ]. There was a slight shift in imaging regions other than the chest (data not shown)[ 31 ]. We also observed that fixed X-ray imaging decreased when adult mobile imaging increased in the emergency setting.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of PCXRs has only increased during the coronavirus disease 2019 (COVID-19) pandemic. Compared to imaging requests prior to the COVID-19 pandemic, studies have shown a near 70% increased demand for PCXRs [2]. The greater volume of imaging requests has made it increasingly difficult for technologists to consistently capture high-quality films for radiologists to interpret [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the COVID-19 pandemic also resulted in an increased utilization of portable chest exams. 1 In our practice, Fuji FDR Go and FDR Go PLUS models (Fujifilm Healthcare, Lexington, MA) are utilized for portable chest radiographs. There were clinical complaints regarding textural artifacts in adult chest images.…”
Section: Introductionmentioning
confidence: 99%
“…Portable digital radiography systems are commonplace in hospital and emergency room settings where a patient's clinical condition may prevent safe transport to a fixed radiography room. Recently, the COVID‐19 pandemic also resulted in an increased utilization of portable chest exams 1 …”
Section: Introductionmentioning
confidence: 99%